Transforming Students' Mathematical Skills with JKT 48 Songs - anggraeni, Nanda Ayu; Choirudin, Choirudin; Ningsih, Eka Fitria; Darmayanti, Rani; Dhakal, Amrit (Delta-Phi: Jurnal Pendidikan Matematika, 2024)
Students' mathematical communication skills are crucial for supporting conceptual understanding and problem solving in mathematics. However, many students still experience difficulties in relating mathematical ideas to everyday situations and clearly explaining mathematical concepts and relationships. This study aims to test the effectiveness of the Auditory Intellectually Repetition (AIR) learning model combined with the JKT 48 song "Fortune Cookie" in improving students' mathematical communication skills. Unlike previous studies that used a qualitative approach, this study employed a quantitative method with a One Group Pretest-Posttest design. The subjects were 23 seventh-grade students at MTs Ma'arif Roudlotut Tholibin Metro. The research instrument was a descriptive test administered before and after the treatment to measure improvements in mathematical communication skills. Data analysis using a paired-sample t-test showed a significant improvement in students' mathematical communication skills after the implementation of the song-assisted AIR model. The average pretest score of 19.21 increased to 81.73 in the posttest. These results indicate that integrating the AIR model with popular songs can be an effective innovation in enjoyable and meaningful mathematics learning